2018
DOI: 10.1186/s12967-018-1515-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of micro-RNA expression profile related to recurrence in women with ESMO low-risk endometrial cancer

Abstract: BackgroundActual European pathological classification of early-stage endometrial cancer (EC) may show insufficient accuracy to precisely stratify recurrence risk, leading to potential over or under treatment. Micro-RNAs are post-transcriptional regulators involved in carcinogenic mechanisms, with some micro-RNA patterns of expression associated with EC characteristics and prognosis. We previously demonstrated that downregulation of micro-RNA-184 was associated with lymph node involvement in low-risk EC (LREC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 93 publications
2
12
0
Order By: Relevance
“…However, to date, few studies have addressed its role in EC, except for a functional study by Li et al [80] demonstrating that miR-34c acts as a tumor suppressor miR in human endometrial cancer 1b (HEC-1b) with the E2F transcription factor 3 (E2F3) being one of the targets. It has also been reported that decreased expression of miR-184 is associated with recurrence in endometrial cancer [81].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, few studies have addressed its role in EC, except for a functional study by Li et al [80] demonstrating that miR-34c acts as a tumor suppressor miR in human endometrial cancer 1b (HEC-1b) with the E2F transcription factor 3 (E2F3) being one of the targets. It has also been reported that decreased expression of miR-184 is associated with recurrence in endometrial cancer [81].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are short non-coding transcripts with 22 nucleotides in length (13). Numbers of studies have demonstrated that miRNAs played significant roles in RNA translation and degradation via binding to the 3 ′ UTR of mRNA (14).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 5 years, up to 754 miRNAs [ 17 ] have been identified as potential biomarkers in EC, some of which are correlated with lymph node involvement, advanced FIGO stage, metastatic status, or histologic type [ 17 , 40 , 103 , 118 , 161 , 162 ]. Increasing our knowledge of the miRNA expression status or the methylation state of key miRNA loci may help to better stratify patients.…”
Section: Discussionmentioning
confidence: 99%